(3QSGdI aj GdEeGeIs - (3CHh HcQ Hf eMeO Hf YHO GdeDef Hf nMpQjR Hf eYnqdj GdMSjfj GdMUfj, Jbqj GdOjf,J (B829 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdBFeI CaVd gPg GdCeI SCdJ CQTOc Gddg hEjGfG Edi WQjb GdMb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B74s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B162 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3cdGe (B92) s
Keywords: (3GdJGQjNs